Hubungan Polimorfisme Genetik Nicotinic Acelycholine Recepttor CHRNB4 dengan Hasil VEP1 dan KVP pada Pasien Penyakit Paru Obstriktif Kronik - Muhammad Haekal Hakim; Setia Putra Tarigan; Amira Permatasari Tarigan; Yuki Yunanda; Noni Novisari Soeroso; Andika Pradana (Jurnal Pengabdian Ilmu Kesehatan, 2026)
Chronic obstructive pulmonary disease (COPD) is a heterogeneous respiratory disorder resulting from interactions between environmental exposure, particularly cigarette smoke, and genetic susceptibility. Variants within thechromosome 15q25 locus encompassing the CHRNA5–CHRNA3–CHRNB4 gene cluster have been associated with smoking behavior, nicotine dependence, and smoking-related diseases, including COPD. The study aimed To evaluate the association between nicotinic acetylcholine receptor CHRNB4 rs1948 polymorphism and spirometric parameters, namely forced expiratory volume in one second (FEV1) and forced vital capacity (FVC), in patients with COPD. This case–control study included 110 subjects (55 COPD patients and 55 controls). COPD diagnosis was established using post-bronchodilator spirometry according to Global Initiative for Chronic Obstructive Lung Disease (GOLD) recommendations. 1 Genotyping of CHRNB4 rs1948 was performed using allele- specific polymerase chain reaction (PCR). Associations between genotype and severity of FEV1 and FVC impairment were analyzed using the Mann–Whitney U test. Mean predicted FEV1 in the COPD group was 38.03 ± 15.19, mean predicted FVC was 57.27 ± 17.03, and mean FEV1/FVC ratio was 50.98 ± 10.82. All COPD patients demonstrated an obstructive spirometric pattern. Compared with controls, COPD patients had significantly lower FEV1, FVC, and FEV1/FVC values (p<0.001). No significant association was observed between CHRNB4 rs1948 genotype and severity of FEV1 (p=0.771) or FVC (p=0.778) impairment. The CHRNB4 rs1948 polymorphism was not significantly associated with spirometric severity in COPD. The contribution of CHRNB4 to COPD may be mediated predominantly through smoking-related behavioral pathways rather than direct effects on lung volumes.